2020
DOI: 10.22335/rlct.v12i2.1168
|View full text |Cite
|
Sign up to set email alerts
|

La violencia en las relaciones de pareja de jóvenes: prevalencia, victimización, perpetración y bidireccionalidad

Abstract: Artículo de investigaciónLa violencia en las relaciones de pareja de jóvenes: prevalencia, victimización, perpetración y bidireccionalidad Violence in the relationships of young couples: Prevalence, victimization, perpetration and bidirectionality A violência nas relações de casais jovens: prevalência, vitimização, perpetração e bidirecionalidade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
6
1
11
Order By: Relevance
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These attitudes indicate confusion and lack of discernment when young people do not determine the limits between normalized treatment and situations of violence. The type of violence detected is bidirectional [ 24 ], used as a method to resolve conflicts in the relationship or because of control and jealousy behaviors that arises regardless of the sex of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Esta violencia, que es utilizada no sólo como forma de ejercicio para la imposición del poder sino también como recurso en la resolución de conflictos, actualmente, se viene manifestando desde nuevas modalidades y afecta a grupos de edad cada vez más bajos (Garrido et al, 2020).…”
Section: │2unclassified
“…Aunque en los últimos años se ha incrementado en nuestro país el número de estudios que señalan la presencia e importancia de la violencia en las parejas jóvenes (Batiza, 2017;Díaz-Aguado et al, 2013;Garrido et al, 2020;Marcos & Isidro, 2019;Martínez et al, 2016;Mohamed et al, 2014;Peña et al, 2018) la línea de investigación sobre ella ha recibido poca atención. Por ello, es necesario disponer de instrumentos válidos y fiables que faciliten el estudio del problema en toda su amplitud y especificidad.…”
Section: │2unclassified
“…Specifically, the debate on the perpetrator's gender, rather than shedding light through its constructs, affects the theory and scientific research, given the diversity and contradictions in its interpretations (Rojas-Solís, 2013). In fact, some research has shown that the predominant violence in relationships at this vital stage is bidirectional (Garrido-Antón et al, 2020;Palmetto, Davidson, Breitbart, & Rickert, 2013;Taylor & Sullivan, 2021). Considering the three typical types of violence of this phenomenon (physical, verbal-emotional, and sexual), studies show that both boys and girls are involved in violence in both roles, as victims and aggressors (Palmetto et al, 2013;Viejo, 2014).…”
Section: Introductionmentioning
confidence: 99%